2004
DOI: 10.1080/0003684042000191147
|View full text |Cite
|
Sign up to set email alerts
|

Who moves? A logit model analysis of inter-provincial migration in Canada

Abstract: This paper addresses the topic of inter-provincial migration in terms of the basic question: 'Who moves?'. Panel logit models of the probability that an individual changes his or her province of residence from one year to the next over the 1982-1995 period are estimated using tax-based longitudinal data. It is found that moving is (i) inversely related to the home province's population size, presumably reflecting local economic conditions and labour market scale effects, while language also plays an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
47
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 19 publications
1
47
0
1
Order By: Relevance
“…The niche public agent offers incentives to enter the niche portion of the more conventional outcomes on interprovincial movers. Finnie (2000) found that age was negatively related to mobility, with younger people being more prone to moving. Edmonston (2002) corroborated this finding, and the IMDB (2000) specified that immigrants 25 to 44 at landing were more likely to move.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The niche public agent offers incentives to enter the niche portion of the more conventional outcomes on interprovincial movers. Finnie (2000) found that age was negatively related to mobility, with younger people being more prone to moving. Edmonston (2002) corroborated this finding, and the IMDB (2000) specified that immigrants 25 to 44 at landing were more likely to move.…”
mentioning
confidence: 99%
“…In addition by 1995 almost half of the 22,595 business immigrants initially admitted to Quebec moved to another province and 17.5% of refugees had left. Nonetheless, Finnie (2000) remains optimistic in light of these observations when he argues that the situation could have been even worse.…”
mentioning
confidence: 99%
See 3 more Smart Citations